Exploring climate nudge attitudes—the significance of perceived climate change knowledge, science trust, and media trust - Jukka Sivonen; Vuokko Härmä; Sakari Karvonen (Humanities & Social Sciences Communications)
Abstract Attitudes toward specific nudges have been extensively studied, but there is a lack of research on attitudes toward climate nudging in a broader sense. This study investigates public attitudes toward climate nudging, utilising Climate Nudge-survey data from 2022 with 2169 respondents in Finland. A novel question set was used to capture attitudes from different perspectives on climate nudging. Employing varimax-rotated factor analysis, two key factors emerged. One was related to collective gains in supporting climate nudging over individual gains, and the other factor was related to perceived advantageousness of climate nudging. Through ordinary least squares (OLS) regression, we explored how these factors associate with perceived knowledge about climate change and trust in science, traditional media, and social media. Positive associations were found between trust in science and traditional media with both factors. However, trust in social media associated slightly negatively with prioritising collective gains. Although perceived climate change knowledge lacked a direct association with both factors, interaction effects revealed that among those with much perceived climate change knowledge, higher trust in science associated with higher scores in both factors. Conversely, high perceived climate knowledge combined with low trust in science was associated with lower scores in both factors. In summary, this study emphasises the pivotal role of public trust in science and traditional media regarding climate nudges’ attitudes and prioritising of collective and individual benefits of climate nudging.